Estratégias de sustentabilidade e identidade das ONGs de assessoria rural num contexto contratualista - Alves, Nára Beatriz Chaves (2012)
From the 90, the State began to decline public services to be executed by civil associations often tucked the notion of Third Sector . In the context of rural development and, more specifically, land reform in the state of Rio Grande do Sul, Incra has hired NGOs to provide technical assistance to settlers and the repercussions of this neu configuration, to the political project of these organizations is not know. This research addresses the issue by performing a contrast of the possibilities of civil society in social critique and change, identified by literature review, with the trajectory of performance of a rural NGO advisory, the Centre for Alternative Technology Popular (Cetap), non-governmental organization created in 1986, with headquarters in Passo Fundo, RS. The case was deal with Cetap qualitative approach, resorting to the literature search, consultation documents, analysis of legislation and conducting semi-structured interviews. The original Cetap s mission stimulate small farms through social organization, encouraging the production so that your organization will guarantee the sustainability and identified themselves and we identified three phases in its history: pre-institucionalization, acting as a center for research, training, demonstration and how NGOs socioambiental and comparative phases shows that networks and parthnerships area shown as essential to defining their lines of action. In its path were marked with the approximations Church, social movements, Network Future Earth and State. The acting in contract began in 2009 to provide services for Ates, Incra and is developed in tandem with other lines of work. The acting in the Ates is seen as converging with the political project of the organization but implies relative loss of autonomy in planning actions. There is a recognition that organizational sustainability implies the need for constant review of its guidelines and that experiences a moment where such revisions are timely.